Integrating a reduced-order model server into the engineering design process. (December 2015) - Suram, Sunil; Bryden, Kenneth M.
Highlights: A reduced-order model server is incorporated into the engineering design process. Proper orthogonal decomposition is used for the reduced-order model. The reduced-order model server stores all data for a particular model. The proposed engineering workflow is compared with a common workflow. The reduced-order model server provides more efficient information exchange. Abstract: Engineering design is a complex and iterative process that involves multiple engineering teams sharing and communicating information during the design process. One aspect of engineering design involves the development of physics-based models and their analysis via numerical simulations that are computationally expensive. To overcome the time constraints due to the complexity of numerical simulations, reduced-order models (ROM) such as proper orthogonal decomposition are being increasingly used. Decreasing the simulation time, however, does not address the inefficiencies in communicating engineering models and analysis during the design process. This paper proposes developing and incorporating a ROM server into the design workflow. The ROM server stores all data associated with a given engineering model and automatically constructs a ROM every time a model is created or updated, thus maintaining a consistent version of information across multiple engineering teams. A common engineering workflow is compared with one using a ROM server. A cost of synchronization metric has been defined based on the parameters of data size, size of the engineering team and design iterations. This metric has been evaluated and compared for the cases with and without a ROM server and it was found that the cost of synchronization is lower when a ROM server is used in the design workflow. It is shown that as the team size increases, the ROM server helps with more efficient information storage and transfer. Finally, an example problem of a heat-exchanger fin shape design is used to demonstrate the ROM server framework.